THE EFFECT OF FLIPPED CLASSROOM ON STUDENTS READING COMPREHENSION AT SMA NEGERI 1 WAWOTOBI - Umar Umar; Asri Nofa Rama (Penerbit Lafadz Jaya, 2022)
The purpose of study is to investigate the effect of flipped classroom on students reading comprehension at SMA Negeri 1 Wawotobi. This study employed a pre-experimental design with one group pre-test and post-test design without control group for quantitative approach. The population of this research was the entire XI IPS 2 students’ of SMAN 1 Wawotobi who enrolled in academic year 2021/2022. The data were obtained from students’ pre-test and posttest scores. The pre-test was given before the treatment applied and the posttest is given after the treatment finished. Results of the study found that there was a significant positive effect of flipped classroom on students’ reading comprehension, p (.000) < 0.05 with the effect size was 3.57. In light of all these findings, flipped classroom significantly affected students’ reading comprehension.